2020
DOI: 10.3390/ijms21144826
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study for the Feasibility of Exome-Sequencing in Circulating Tumor Cells Versus Single Metastatic Biopsies in Breast Cancer

Abstract: The comparison of the landscape of somatic alterations in circulating tumor cells (CTCs) versus metastases is challenging. Here, we comprehensively characterized the somatic landscape in bulk (amplified and non-amplified), spike-in breast cancer cells, CTCs, and metastases from breast cancer patients using whole-exome sequencing (WES). We determined the level of genomic concordance for somatic nucleotide variants (SNVs), copy number alterations (CNAs), and structural variants (SVs). The variant allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…To get one step forward, and acknowledging both, the growing trend of last decades towards de-escalating surgical procedures not only on primary breast cancer but also on axillary nodes 10,12 , and the technical difficulties of sampling and processing different metastatic sites 13 , we hypothesized that liquid could replace tissue biopsies. Indeed, although rather preliminary, our data support the role of CTCs as a tissue-surrogate.…”
Section: Discussionmentioning
confidence: 99%
“…To get one step forward, and acknowledging both, the growing trend of last decades towards de-escalating surgical procedures not only on primary breast cancer but also on axillary nodes 10,12 , and the technical difficulties of sampling and processing different metastatic sites 13 , we hypothesized that liquid could replace tissue biopsies. Indeed, although rather preliminary, our data support the role of CTCs as a tissue-surrogate.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-seq method described above was validated in whole-transcriptome profiling studies in CTC from patients with non-metastatic breast cancer (stage II-III). These studies’ procedures and results were previously reported [ 28 , 29 ], and the results demonstrated that CTCs from patients with MBC could be used to generate cDNA libraries of sufficient quantity and quality that enable whole-genome sequencing.…”
Section: Methodsmentioning
confidence: 54%
“…The formidable heterogeneity of breast cancer forbids us from covering all patients with a single treatment strategy ( 18 ). Additionally, over the lengthy course of treatment, tumor cells frequently undergo mutation, resulting in resistance to the existing treatment regimens ( 19 ). This condition spurs us to delve more deeply into breast tumor cells’ physiological processes and discover the mechanisms underlying their development and death.…”
Section: Discussionmentioning
confidence: 99%